The complex interplay between exchange rate and real markets: An agent-based model exploration - Domenico Delli Gatti; Tommaso Ferraresi; Filippo Gusella; Lilit Popoyan; Giorgio Ricchiuti; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
We extend the multi-country, multi-sector agent-based model in Dosi et al. (2019, 2021) by incorporating an exchange rate market where heterogeneous chartist and fundamentalist financial traders exchange foreign currencies. This introduces complex interactions between the real and financial side of the economies that reverberate on the dynamics of the exchange rate, which acts both as a transmission channel of endogenous fluctuation and as a source of shocks. Simulation results show that model is able to account for a rich ensemble of stylized facts (e.g., fat tails, volatility clustering, fluctuations and contagion among others) concerning the exchange market and its interactions with the real economy dynamics at different level of aggregation. Moreover, our findings reveal that speculative behavior in the exchange rate market substantially increases financial turbulence and contributes to real economic fluctuations. On the policy side, we highlight the power and limitations of central bank interventions in the exchange rate market.
Keywords: E3; F41; O4; O41; 330; agent-based model; exchange rate dynamics; financial crises; endogenous business cycles; heterogeneous traders; central bank interventions